Perception of Physical Education Students Regarding The Use of TWS (True Wireless Stereo) When Jogging on Ear Health - Reza Hafizd Hermawan; Encep Sudirjo; Dinar Dinangsit (Universitas Tadulako, 2026)
This study was motivated by the increasing use of true wireless stereo (TWS) devices among university students while jogging, which potentially increases ear health and safety risks. Previous studies have addressed the impact of audio devices on physical performance. Physical education students differ from the general student population due to their higher intensity of physical activity, including regular jogging as part of their academic routine and lifestyle. This leads them to use TWS devices more frequently and for longer durations, especially during dynamic physical activities. This study used a qualitative case study approach with 15 participants, including 13 university students and 2 ENT specialists, for source triangulation. Data collection techniques included observation, interviews, and documentation, with data analysis using NVivo 12 software and participant data collection using a purposive sampling technique. The results showed that most university students used TWS devices for more than 60 minutes and at volume levels above 60%, both during jogging and other activities. While this use has positive effects, such as increased motivation, reduced fatigue, and greater comfort during exercise, negative effects have also been reported, including tinnitus (ringing in the ears), pain, dizziness, and decreased awareness of the surrounding environment, which can increase the risk of accidents. Source triangulation with an ENT doctor increases the risk of hearing loss from prolonged exposure to excessive noise. Therefore, education and awareness are needed to implement safe TWS use and maintain ear health.